PENGARUH SISTEM PEMBERIAN KREDIT TERHADAP TINGKAT NON PERFORMING FINANCING (NPF) STUDI KASUS PADA BSI KCP MANGGENG - Dini Febriani; Dewi Sartika (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study aims to examine the effect of the credit system on the level of Non-Performing Financing (NPF) at BSI KCP Manggeng. This associative study uses the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, and coefficient of determination test as data analysis techniques. This study included 634 customers of BSI KCP Manggeng in 2020-2021 who utilized the credit system. The sampling method used was purposive sampling with a total of 72 respondents. Primary and secondary data were collected from the entity's financial statements and questionnaire distribution. The data analyzed with the help of SPSS Statistics 20 Software. The results of this study indicated that the credit system has a positive and significant effect on the level of non-performing financing (NPF) at BSI KCP Manggeng. Therefore, the entity should employ more stringent marketing methods and gain a more in-depth understanding of the debtor's business and character to determine the appropriate ability to pay and to appoint credit capital to ensure that the credit system operates efficiently and is used to advance the debtor's business.